Women Leaders at Work - Ghaffari, Elizabeth; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
"Women Leaders at Work traces the personal life decisions taken by women who found ways to achieve greatness in their work. Each story is intriguing. But, collectively, the stories provide inspiration. They illustrate how real women of varied talents from varied backgrounds traversed quite different paths, seized opportunities presented in many guises, and found ways to achieve and to contribute to society. Elizabeth Ghaffari relates these stories with an unerring instinct to reveal the fascinating, personal dimensions of real women." Anita K. Jones, University Professor Emerita, University of Virginia "Women Leaders at Work shines a light on women. Today's leaders who are women, who are changing our world, even as examples, inspire young women who are our leaders of the future. Great book!" Frances Hesselbein, President & CEO,Leader to Leader Institute, New York, NY "The stories of each of these amazing women read like novels -- humble beginnings, triumphs, failures, incredible determination and resourcefulness, overcoming the familiar obstacles facing women in the workplace. But these stories are true, and they inspire us. There are many more stories out there, but thanks to Elizabeth Ghaffari, we are privileged to share these few. Groundbreaking women, groundbreaking book." Judith M. Runstad, Attorney, FOSTER PEPPER PLLC,Seattle, WA "I have read many books on leadership and women leaders, and Elizabeth Ghaffari$1 (Bs book rises to the top for me. The in-depth interviews provide insight into leadership in general, issues unique to women, as well as an insider$1 (Bs view into a broad array of industries. Women Leaders at Work highlights superb women leaders, beyond the "usual suspects," many of whom you may never have otherwise come to know." Cathy Sandeen, Ph.D., MBA, Dean, UCLA Extension, University of California, Los Angeles "In her newest book, Elizabeth Ghaffari has scouted out exceptional women who started in small, but courageous ways to follow unique visions. These women achieved positions of influence and power, but their routes to success were never straight-lined. They endured digressions and embraced change. They navigated the intricacies of corporations, academia, non-profits, and the fields of science and technology. They speak with their own voices about their lives and motivation and tell their stories with modesty and encouragement to other women who may want to lead and serve." Mary S. Metz, Ph.D., President Emerita, Mills College "Women Leaders at Work is filled from cover-to-cover with stories about the lives of extraordinary women who are in leadership today. Elizabeth Ghaffari uses her exceptional interviewing talents to ask the right questions to elicit memorable lessons that are inspiring, uplifting and educational. Each of the eighteen chapters focuses on the life and career path of a fascinating, accomplished woman. Ghaffari illustrates that breakthrough success can occur in a myriad of fields from medicine, law, academia, government, public corporations, science and philanthropy. It is not necessary to stay on a narrow hierarchical career path. In fact, none of these champions followed career paths that were straight-line trajectories. 'We often have to be re-potted to grow' and 'Don$1 (Bt leave the power of a corporation just because you want to change the world. Harness it,' are two of the many memorable lessons. Women Leaders at Work is filled with important wisdom and advice for past, present and future leaders. I highly recommend this book for men and women of all ages and interests!" Susan Murphy, Ph.D, noted author, speaker, business consultant, www.Consult4Business.com "Ghaffari's Women Leaders at Work captures diverse personal stories of trailblazing women who share candid experiences including career challenges. It is clear that much more than mentoring matters -- sponsorship is key." Linda Griego, President & CEO, Griego Enterprises, Inc. In Women Leaders at Work, skilled interviewer Elizabeth Ghaffari speaks to women at or near the top of their professions in a wide array of fields. In part, the book focuses on how they did it: how they prepared, how they overcame obstacles, how they achieved major milestones, and how they took the unconventional turn in the career path that made all the difference. Each chapter is also a gem that contains invaluable insights into gaining and using power responsibly. Every interview shows how female leaders make a difference on a day-to-day basis: charting strategy, managing senior managers and key partners, allocating resources, influencing stakeholders and the public, handling internal problems and competitive challenges, launching initiatives, or pouncing on opportunities the rest of us can$1 (Bt see. This book, like the others in the bestselling Apress At Work series, provides readers with a range of examples and experiences they can use to achieve their own goals. It details key actions or decisions that will help women reach the C-level, win public office, or achieve professional recognition and status. By tapping the wisdom and astute advice of contemporary women in leadership, Women Leaders at Work provides an up-to-date guide for ambitious women seeking professional success. This book: Showcases successful women in leadership positions in the modern millennium Explains how they prepared to take on the challenges leadership imposes Provides advice for those who would follow in their footsteps Demystifies career success for women Other books in the Apress At Work Series: Coders at Work, Seibel, 978-1-4302-1948-4 Venture Capitalists at Work, Shah & Shah, 978-1-4302-3837-9 CIOs at Work, Yourdon, 978-1-4302-3554-5 CTOs at Work, Donaldson, Seigel, & Donaldson, 978-1-4302-3593-4 Founders at Work, Livingston, 978-1-4302-1078-8 European Founders at Work, Santos, 978-1-4302-3906-2 Advertisers at Work, Tuten, 978-1-4302-3828-7 Gamers at Work, Ramsay. 978-1-4302-3351-0s
Keywords: Economics; Economics/Management Science; Business/Management Science, general